Assistance in the Preparation of Village Policies and Regulations on Pattumea Village Tourism in Betteng Village, Pamboang District - Abdul Hafid; Muhammad Sajidin; Sulaeman; Budi Prayetno (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Assistance in the preparation of tourism village policies and regulations in Betteng Village, Pamboang District, can encourage sustainable tourism management and improve community welfare through the utilization of local potential. This mentoring process involves analyzing tourism potential, identifying challenges, and drafting regulations that support the development of community-based tourism destinations. The service activity was carried out with the aim of providing assistance in the preparation of village policies and regulations related to tourism development in Betteng village. This is one of Betteng Village's efforts to increase the village's own income. This process involves village communities, village officials, and other stakeholders through a series of focus group discussions (FGD), interviews, and direct observations. A participatory approach is used to ensure the active involvement of the community in the policy formulation process, so that the resulting policies are in accordance with local needs and aspirations. Situation analysis and mapping of tourism potential are carried out to identify opportunities and challenges in tourism development. From the results of the analysis, draft village policies and regulations were prepared that support community-based and sustainable tourism management. The results of this activity are in the form of village policy documents and regulations that regulate village tourism governance in a structured manner, which is expected to improve the quality of tourism, the local economy, and the welfare of the community in Betteng Village. Assistance in the preparation of tourism village policies and regulations in Pattumea Village and Betteng Village has succeeded in producing structured policy and regulatory documents. By using participatory and collaborative methods, the policies prepared are expected to support sustainable community-based tourism management, improve the quality of tourism, and local economic welfare through strengthening village institutions and active community involvement.